Aprendizagens complexas: quatro teses provisórias para a educação contemporânea - Shaw, Míriam Ribeiro de Barros (2017)
This research is in the school environment, it is about the practices of teachers and managers of the Colégio Santo André, São José do Rio Preto, during the period from 2011 to 2015. The key question, research problem of this study is how to charm, to encourage students, educators into the adventure of knowing? Desires, the specific objectives of this study are to observe the practices of educators that stimulate the taste for thinking, studying, discovering; identify obstacles encountered by educators in this way; verify that the multidisciplinary and interdisciplinary activities favour the taste for study. The ideas that inspired reflection, the hypotheses of this research are the many activities, transdisciplinary promote students' interest in the taste for study, discover, invent; ethical, imaginative and emotional attitudes are fundamental to the practices that stimulate the taste for knowledge of educators and students. Fieldwork was conducted in two phases: the first phase, there were two collective projects with members of the community; questionnaire evaluation was answered by teachers; data tabulation, analysis and discussion of the results in the years 2011 and 2012 were discussed by directors and coordinators; in the second phase, between 2013 and 2015 were carried out: review of literature, specific interviews with educators, the final report writing. Two key references guide this research: education is one of the regeneration pathways of contemporary society; need to reform the thought of educators and students. The teaching-learning of understanding, hearing; imagination, reinvention; ethics, recognition; affection, love is presented as four provisional proposals for contemporary education. Complex Learnings